Step-by-step explanation:
2sin(x)cos(x) - sin(x) + 2cos(x)-1= 0
<=> sinx( 2cosx -1) + ( 2cosx -1) =0
<=> (sinx +1) + ( 2cosx-1)=0
<=> sinx=-1 or cosx= 1/2
+) sinx=1 => x= pi/2 + k×2pi
+)cosx=1/2 => x= pi/3+ k×2pi or x=-pi/3 + k×2pi
x€ [0,2pi] => x= pi/2, pi/3.
Answer:
x=−3y+36
Step-by-step explanation:
2/7x - 2/5x = 8
multiply both sides by 35
= 10x - 14x = 280
combine 10x and 14x
= -4x = 280
divide both sides by -4
x= -70
Answer:
x = -9
Explanation:
(3x + 9)^5 = 32x^5
(3 (x + 3))^5 = 32x^5
3^5 (x + 3)^5 = 32x^5
243(x + 3)^5 = 32x^5
243(x + 3)^5 - 32x^5 = 0
x = -9
Answer: y=8 m=5
Step-by-step explanation: